Pelatihan Pemasaran Digital Bagi Pelaku UMKM Desa Dukuhmojo-Mojoagung Menggunakan Media Sosial WhatsApp dan Instagram - Khotim Fadhli; Wisnu Siwi Satiti; Lailatus Sa'adah; Tiara Pratiwi; Sindi Pradita; M. Adi Maulana; Moh. Syarifudin (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Advances in information technology have had a significant impact on various aspects of life, one of which is the economic sector. Buying and selling activities are one of the main components of economic activity. Initially buying and selling activities depended on conventional markets which were carried out directly. However, with the development and advancement of technology, buying and selling activities have become more common and efficient. One sector that carries out buying and selling is Micro, Small and Medium Enterprises (UMKM). Along with advances in technology, MSME players should also adapt the form of marketing and sales they carry out, namely by making optimal use of digital marketing. As an effort to help UMKM carry out digital marketing, community service activities are carried out in the form of digital marketing training. Partners in this activity are MSMEs in Dukuhmojo Village, Mojoagung District, Jombang Regency, East Java. This community service activity is carried out using the Asset Based Community-Driven Development (ABCD) method. Adopting this method, community service activities are carried out in the form of training for partners, with a focus on digital marketing using social media Instagram and WhatsApp media. The results of the activity show that the training is effective in increasing partners' knowledge about digital marketing. Apart from that, MSME players stated that they were helped by the assistance from the service team, especially in terms of technical marketing using Instagram social media.